Issues, requirements and support for location-intensive mobile commerce applications. (1st January 2003) - Varshney, Upkar
With advances in wireless networking, devices, applications and middleware, a new area of applications has emerged. Termed mobile commerce, these applications have attracted some interest among researchers, developers, carriers, and content providers. One major issue is the location management support that is needed by many location-intensive mobile commerce applications, such as user and location-specific mobile advertising, mobile inventory management, wireless-business reengineering, and mobile financial services. In this paper, we address the location requirements of m-commerce applications from the user, provider and networking perspectives. We also discuss how such requirements may be supported by the exiting and emerging wireless networks. We also present and discuss several open and interesting research problems.